Optimising enteral nutrition in growth restricted extremely preterm neonates – a difficult proposition. (2nd November 2015) - Shah, P.; Nathan, E.; Doherty, D.; Patole, S.
Abstract: Background : Optimising enteral nutrition of extremely preterm neonates (EP: Gestation <28 weeks) with intrauterine growth restriction (IUGR) has always been difficult considering their higher risk of necrotising enterocolitis (NEC), and frequency of feed intolerance. Aim : To evaluate the nutritional outcomes in EP neonates with IUGR. Methods : Data on demographic characteristics, feeding details (e.g. type of milk, postnatal age at start), and outcomes to discharge or death were collected from the medical notes for all EP neonates, who survived first 72 h of life, between January 2009 and December 2010. A standardised feeding protocol was followed during the study period. Results : 38/220 (17.3%) EP neonates admitted during the study period had IUGR. The mean (IQR) age at start of minimal enteral nutrition [7 (5–10) versus 5 (4–8) days, p = 0.005), and nutritional (1 ml/2hourly) feeds [12 (8–15) versus 9 (7–13) days, p = 0.034] was significantly delayed in IUGR compared to non-IUGR neonates. IUGR neonates reached full enteral feeds (150 ml/kg/day) at a significantly late median (IQR) postnatal age [32 (21–40) versus 24 (17–31) days, p = 0.009), taking longer time to achieve this milestone [20 (15–34) versus 16 (12–4) days, p = 0.008). The incidence of postnatal growth restriction was significantly higher in IUGR versus non-IUGR (73% versus 45%, p = 0.003) neonates. The incidence of ≥ Stage II NEC was low [18/220 (8.1%)] to make valid statistical comparisons. Conclusion : Optimising enteral nutrition in growth restricted extremely preterm neonates is difficult using the current strategies for enteral nutrition.